Solitary Mastocytoma of the Vulva - Shasi Velusamy; Jayasree Karuthedath Areeppurath Mana; Chalissery Francis Mathew (Case Reports in Pathology)
Solitary mastocytoma of the skin is a rare tumor. Its occurrence in the vulva is extremely rare with only few case reports in the literature. We report a solitary mastocytoma of the vulva in a 10-year-old girl. Her systemic examination was unremarkable. The clinical and histopathological features were consistent with the diagnosis of solitary mastocytoma of the vulva. The follow-up after surgical excision was uneventful. The purpose of this communication is (i) to report a case of solitary mastocytoma occurring in an unusual site, the vulva and to show that (ii) in this case age at presentation is 10 years with infancy as common age of presentation of solitary mastocytoma, and to show that (iii) in appropriate setting this should be included in the differential diagnosis of vulval swelling.